Differences in the protective capabilities of bicycle helmets in real-world and standard-specified impact scenarios. (28th February 2018) - Bland, Megan L.; Zuby, David S.; Mueller, Becky C.; Rowson, Steven
ABSTRACT: Objective : The purpose of this study was to investigate relative differences in impact attenuation capabilities of bicycle helmets under real-world impact conditions and safety standard-specified conditions using a standard rig. Methods : A Consumer Product Safety Commission (CPSC) test rig was used to impact 10 helmet models of varied design. Impact configurations included 2 locations and 2 velocities. A frontal rim location (inferior to the standard-defined test area) and a temporal location were selected to reflect common cyclist impacts. An impact velocity of 3.4 m/s, an average normal impact velocity in cyclist accidents, was selected, as well as the CPSC standard velocity of 6.2 m/s. Four samples per helmet model were subjected to each of the 4 impact configurations once (randomized test order per sample), resulting in 160 drop tests. Peak linear acceleration (PLA) and head injury criterion (HIC)-based Abbreviated Injury Scale (AIS) ≥ 4 brain injury risk were determined and compared across helmets and impact configurations using analysis of variance. Other impact characteristics such as duration, effective liner stiffness, and energy dissipated were also calculated from acceleration data. Results : Helmet performance varied significantly between models. PLA ranged from 78 to 169 g at 3.4 m/s (0–2% AIS ≥ 4 brain injury risk) and 165–432 g (10–100% risk) at 6.2 m/s. Temporal impacts resulted in higher PLAs than frontal impacts, likely due to increased effective liner stiffness. However, 2 helmets exceeded the CPSC pass–fail threshold (300 g) at the frontal rim location, producing >70% risk. Force–displacement curves suggest that bottoming-out occurred in these impacts. Aside from bottoming-out cases, helmets that performed worse in one impact configuration tended to perform worse in others, with non-road-style helmets among the worst. Conclusions : The 10 bicycle helmets tested produced considerable differences in their protective capabilities under both real-world and standard-specified conditions on the CPSC rig. Risk of severe brain injury varied widely between helmets at the standard impact velocity, whereas the common, lower severity impacts produced PLAs associated with concussion. Helmets of a nonroad style generally performed worse across configuration. The temporal location produced higher risks for most helmets, although some helmets were found to offer inadequate protection at the helmet rim. Because this is a commonly impacted location in cyclist accidents, there may be benefit to expanding the testable area in standards to include the rim. Results from this study demonstrate the value in testing nonstandard conditions and can be used to inform standards testing and helmet design.